Physically-Based Animation in Performing Accuracy Bouncing Simulation - Loh, Ngiik Hoon (2020)
This study investigates the useof physics formulasin achieving plausible bouncing simulationin animation. The needforphysics animation was to produce visually believable animations adhering to the basic laws of physics. Based on the review, the creation of accurate timing simulation in bouncing dynamic was significantly difficult particularlyin setting keyframes. It was comprehensible that setting the value ofkeyframes was unambiguous while specifying the timing forkeyframeswas a harder task and often time-consuming. The case study of bouncing balls’ simulation was carried out in this research and the variables of mass, velocity, acceleration, force,and gravity are taking into consideration in the motion.However, the bouncing dynamic is a significant study in animation. It is often used and it shows many different aspects of animations, such as a falling object, walking, running, hopping,and juggling. Therefore, the physical framework was proposed in this study based on numerical simulations, as the real-time animation can be addressed for controlling the motion of bouncing dynamic object in animation. Animation based physics algorithm provided the animator the ability to control the realism of animation without setting the key frame manually, to provide an extra layer of visually convincing simulation.